DEVELOPMENT OF INCREASING THE NATIONAL SPORT POTENTIAL IN UZBEKISTAN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The use of national sports in physical education classes develops such as speed and strength, flexibility, endurance and others. One of the important aspects of the training process, its effectiveness is the construction of classes using national sports of Uzbekistan. National sports affect the education of the will, the moral feelings, the development of intelligence, speed of reaction, physically to strengthen the child. It fosters a sense of responsibility to the team, the ability to act in a team. Apparently, such a wide application of folk sports and ensures their preservation and transmission from generation to generation.